Enhancing farm productivity and profitability by technological interventions through farmers’ participatory approach in Hisar district - Malik, Anil Kumar; Sheoran, R S; Verma, Tarun; Bidhan, Devender; Dalal, Rajpal; Chahal, P K (Indian Farming, 2022)
.